Effects of fatigue induced by prolonged gait when walking on the elderly - Pereira, Marcelo [UNESP]; Gonçalves, Mauro [UNESP] (Termedia Sp. z.o.o., 2011)
Purpose. Fatigue has been pointed as a fall risk in the elderly; however, the effects of prolonged gait on neuromuscular recruitment and on its pattern remain unknown. The aim of this study was to evaluate the effects of prolonged gait on neuromuscular recruitment levels and spatial-temporal gait variables. Methods. Eight healthy older women (age: 72.63 ± 6.55 years) walked at their preferred walking speed for twenty minutes on a treadmill. The Root Mean Square (RMS) from the vastus-lateralis, femoral biceps, tibialis anterior and lateral gastrocnemius muscles were determined at the first and last minute of the test during the moments of Heel Strike (HS), Terminal Stance and Terminal Swing (TS). In addition, coactivation in the knee and ankle as well as the stride cadence and length were measured in the test. The two RMS data (taken at the first and last minute) were compared by means of a Student's t-test. Results. Twenty minutes of walking induced fatigue in the subjects, as observed through an increase in RMS, notably during the HS and TS. Coactivation was also influenced by the prolonged gait test. The only gait phase where a risk of falling was enhanced was the HS. Nonetheless, subjects developed strategies to maintain a safe motor pattern, which was evidenced by an increase in stride length and a decrease in stride cadence. Conclusion. Tests lasting just twenty minutes on a treadmill were enough to induce fatigue in older adults. However, the level of fatigue was not enough to present a danger or fall risk to elderly individuals.
Keywords: ageing; electromyography; fatigue; kinematic; walking